A Network-Guided Genetic Approach to Identify Novel Regulators of Adventitious Root Formation in Arabidopsis thaliana - Ibáñez, Sergio; Ruiz-Cano, Helena; Fernández, María Á.; Sánchez-García, Ana Belén; Villanova, Joan; Micol, José Luis; Pérez-Pérez, José Manuel (Frontiers in Plant Science, 2019)
Adventitious roots are formed de novo during post-embryonic development from non-root tissues, in processes that are highly dependent on environmental inputs. Whole root excision from young seedlings has been previously used as a model to study adventitious root formation in Arabidopsis thaliana hypocotyls. To identify novel regulators of adventitious root formation, we analyzed adventitious rooting in the hypocotyl after whole root excision in 112 T-DNA homozygous leaf mutants, which were selected based on the dynamic expression profiles of their annotated genes during hormone-induced and wound-induced tissue regeneration. Forty-seven T-DNA homozygous lines that displayed low rooting capacity as regards their wild-type background were dubbed as the less adventitious roots mutants. We identified eight lines with higher rooting capacity than their wild-type background that we named as the more adventitious roots mutants. A relatively large number of mutants in ribosomal protein-encoding genes displayed a significant reduction in adventitious root number in the hypocotyl after whole root excision. In addition, gene products related to gibberellin biosynthesis and signaling, auxin homeostasis and xylem differentiation were confirmed to participate in adventitious root formation. Nearly all the studied mutants tested displayed similar rooting responses from excised whole leaves, which suggest that their affected genes participate in shared regulatory pathways required for de novo organ formation in different organs.